To the fiftieth anniversary of the KIPT torsatron program - Voitsenya, V.S.; Bykov, V.E.; Rudakov, V.A.; Bondarenko, V.N.; Garkusha, I.E. (Вопросы атомной науки и техники, 2020)
The paper is dedicated to the 50th anniversary of controlled thermonuclear fusion studies performed at the KIPT on the specific stellarator-type experimental installations commonly referred to as “the torsatron”. Detailed data are reported on the operating thermonuclear facility “Uragan-2M”, the research results obtained with it, and also, the prospects for its use as a reactor. The advantages of the torsatron of this type are described, among them being the wide-range parameter variation capability. This is of importance for finding out the regularities related to plasma stability, heating and confinement. Робота присвячена 50-річчю досліджень у ХФТІ з проблеми керованого термоядерного синтезу на експериментальних установах спеціальної конструкції, яку прийнято називати торсатроном. Детально освітлені особливості конструкції діючої термоядерної установки торсатрона “Ураган-2М”, результати досліджень на ній та її реакторні перспективи. Відзначені достоїнства такого типу пристрою, що виражаються в можливостях широкої зміни параметрів, що важливо для встановлення закономірностей, пов’язаних із стійкістю, нагрівом і утриманням плазми. Работа посвящена 50-летию исследований в ХФТИ по проблеме управляемого термоядерного синтеза на экспериментальных установках специальной конструкции, которую принято называть торсатроном. Подробно освещены особенности конструкции действующей термоядерной установки торсатрона “Ураган- 2М”, результаты исследований на ней и ее реакторные перспективы. Отмечены достоинства такого типа устройства, выражающиеся в возможностях широкого изменения параметров, что важно для установления закономерностей, связанных с устойчивостью, нагревом и удержанием плазмы.